Signal transducer and activator of transcription 3 (STAT3) promoter methylation and expression in pituitary adenoma - Indre Valiulyte; Giedrius Steponaitis; Daina Skiriute; Arimantas Tamasauskas; Paulina Vaitkiene (BMC, 2017)
Abstract Background Pituitary adenoma (PA) is a benign brain tumor that can cause neurological, endocrinological and ophthalmological aberrations. Till now there is a need to identify factors that can influence the tumor invasiveness and recurrence. The aim of this study was to evaluate the associations between the signal transducer and activator of transcription 3 (STAT3) promoter methylation, mRNA expression and the invasiveness or recurrence of PAs and patient clinical characteristics. Methods Study participants comprised of 102 subjects with a diagnosis of PA: 54 functioning and 48 non-functioning, 58 invasive and 30 non-invasive PAs and 14 relapses. The bisulfite treatment of tumor DNA and methylation-specific polymerase chain reaction (MS-PCR) method was used to determine the STAT3 gene promoter methylation. For the STAT3 mRNA expression, the first-strand cDNA was produced from total RNA by using reverse transcriptase and quantitative real-time PCR (qRT-PCR) was performed. Results In 10.78% (11/102) of PA tissues STAT3 gene promoter was methylated. A gender of male and patient group older than 60 years were significantly associated with reduced STAT3 mRNA expression (Mann-Whitney test, p = 0.025, p = 0.047, respectively). However, no more statistical differences were found between STAT3 promoter methylation, mRNA expression and patient clinical characteristics or PA invasiveness or recurrence. Conclusions Further investigations are needed to clarify the influence of STAT3 gene promoter methylation and mRNA expression changes in PAs.